Pengaruh Persepsi Harga Terhadap Loyalitas Pelanggan Melalui Kepuasan Konsumen Sebagai Variabel Intervening Pada PT. Isuzu Mobilindo Plaza Kota Makassar - A. Afifah Humairah; Burhanuddin Burhanuddin; Nurul Fadilah Aswar; Isma Azis Riu; Rahmat Riwayat Abadi (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aims to analyze the influence of price perception on customer loyalty via consumer satisfaction as an intervening variable at PT. Isuzu Mobilindo Plaza in Makassar City. The study considers price perception as the independent variable, customer loyalty as the dependent variable, and consumer satisfaction as the intervening variable. The population studied were consumers of PT. Isuzu Mobilindo Plaza products at least three times and who live in Makassar City and are aged 28–60 years. PT. Isuzu Mobilindo Plaza products at least three times and have used PT. Isuzu Mobilindo products for at least three years. A total of 104 people were selected for the study using a purposive sampling technique. The study employed a quantitative approach with a Structural Equation Modelling – Partial Least Squares (SEM-PLS) data analysis technique, using SmartPLS 3.2.9 software. The results indicate that price perception has a positive and significant effect on consumer satisfaction and customer loyalty. Additionally, the final results show that consumer satisfaction mediates the effect of price perception on customer loyalty.